Regulation of CARD8 Expression by ANRIL and Association of CARD8 SNP rs2043211 (p.C10X) with Ischemic Stroke - Bai, Ying (2014)
BACKGROUND AND PURPOSE: ANRIL has long been considered as the strongest candidate gene at the 9p21 locus, robustly associated with stroke and coronary artery disease (CAD). However, the underlying molecular mechanism remains unknown. The present study works to elucidate such a mechanism. METHODS: Utilizing eQTL analysis we identified potential genes whose expression may be influenced by genetic variation in ANRIL. To verify the identified gene(s), knockdown and over-expression of ANRIL was evaluated in HUVECs and HepG2 cells. Ischemic stroke and CAD risk was then evaluated in the gene(s) demonstrated to be mediated by ANRIL in 3 populations of Chinese Han ancestry; two ischemic stroke populations including the Central China cohort (903 cases and 873 controls) and the Northern China cohort (816 cases and 879 controls), and one CAD cohort consisting of 772 patients and 873 controls. RESULTS: eQTL analysis identified CARD8 among others, with knockdown of ANRIL expression decreasing CARD8 expression and over-expression of ANRIL increasing CARD8 expression. The minor T allele of a previously identified CARD8 variant (rs2043211) was found to be significantly associated with a protective effect of ischemic stroke under the recessive model in two independent stroke cohorts. No significant association was found between rs2043211 and CAD. CONCLUSION: CARD8 is a downstream target gene regulated by ANRIL. SNP rs2043211 in CARD8 is significantly associated with ischemic stroke. ANRIL may increase the risk of ischemic stroke through regulation of the CARD8 pathway.